Strategi Hilirisasi Tanaman Purun menjadi Harta Karun di Kalimantan Selatan: Downstream Strategy of Purun Plant into A Treasure in South Kalimantan - Fadhillah, Anas; Auliana, Putri Eka; Samsudin, Rofik (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2024)
Purun plants are a treasure for some people who live in peatland areas. These plants can be used to make high-value goods/crafts and improve the local economy. In addition, purun plants have the potential to be the Regional Original Income (PAD) of South Kalimantan. Because they can be made into crafts such as hats, straws, bags, and mats that are sold to tourists. However, various obstacles arise, including capital, product improvement, product innovation, and scarcity of raw materials for products. The purpose of this study is to analyze the optimization strategy for developing purun craft products that are right for the people of South Kalimantan using a quantitative approach and the SWOT analysis method. The data used is secondary. The results of this study are included in quadrant I, the strategy that must be applied in this condition is to support an aggressive growth policy. For this reason, strategies and schemes are needed, including forming cooperatives, regulating the use of purun products, training in developing purun products, getting injections from investors, participating in exhibitions, involving government and banking intervention, and intensifying green economy campaigns. The suggestion from the results of this analysis is that the development of purun products should continue to be developed because they use environmentally friendly materials, and there needs to be guidance and regulation from the government.